“Managing the hungry and disciplining the poor”: A critical examination of the paradox of food insecurity policy in Canada and the transformative power of narrative - Burton, Laurel (Université d'Ottawa | University of Ottawa, 2024)
Over forty years ago the first food bank opened in Canada, marking the beginning of an institutionalized system that would replace social welfare policies as the primary way to “…help Canadians put food on the table ”. Household food insecurity in Canada refers to inadequate or insecure access to food due to financial constraints. Research overwhelmingly shows that income redistribution policies are far more effective at reducing food insecurity than food charity or other food (re)distribution interventions. Yet, institutionalized food programs continue to dominate policy discussions, even as food insecurity rates soar to unprecedented levels across the country. There is a paradox here: despite clear evidence that income inequality drives food insecurity in Canada, governments consistently fail to implement effective income redistribution policies, opting instead for ineffective food programming. In their book, Why isn’t government policy more preventive (2020), Cairney & St Denny explore the intersection of three policy theories – Multiple Streams Approach (MSA), Social Construction and Policy Design (SCPD), and Complexity Theory – offering a nuanced framework for understanding why prevention policy consistently challenges governments. This paper applies these theories to the paradox of food insecurity policy in Canada, using it as a compelling case study of how governments struggle to implement effective prevention policies, despite their potential to significantly improve public health outcomes. Key words: prevention policy; multiple streams analysis; social construction and policy design; complexity theory; household food insecurity; food insecurity; charity; food banks 2 The Hon. Marie-Claude Bibeau, Minister of Agriculture and Agri-Food: Office of the Prime Minister of Canada. (2020). Prime Minister announces additional support for food banks and local food organizations.